At the intersection of cultural and natural heritage: Distribution and conservation of the type localities of Italian endemic vascular plants. (October 2017) - Brundu, Giuseppe; Peruzzi, Lorenzo; Domina, Gianniantonio; Bartolucci, Fabrizio; Galasso, Gabriele; Peccenini, Simonetta; Raimondo, Francesco Maria; Albano, Antonella; Alessandrini, Alessandro; Banfi, Enrico; Barberis, Giuseppina; Bernardo, Liliana; et al.
Abstract: We conducted a GIS spatial analysis with the aim of providing the first quantitative large-scale overview of the distribution patterns of 1536 type localities ( loci classici ) of 1216 Italian endemic vascular plants and their relationship with a set of descriptive variables. Whereas some variables were used to model the presence-absence distribution patterns of the type localities for the whole set of endemics as well as for the subset of narrow endemics, others (e.g., presence inside or outside protected areas and Italian Important Plant Areas) were considered with the purpose of assessing potential assets or risks for conservation. The largest number of type localities was found within the Mediterranean biogeographic region (1134), followed by the Alpine region (306) and Continental region (96). A total of 670 locations are located on islands, whereas 866 are located on the Italian mainland (139 and 124 in the case of narrow endemics, respectively). A large number of type localities are located in mountainous areas and along the coastline, which can be seen as a potential risk for conservation. On the contrary, we detected a positive correlation with the distance from roads, which might be considered to be an asset. Importantly, 1030 type localities fall inside protected areas, whereas 506 localities fall outside protected areas, with 259 of these unprotected localities on islands. We propose considering the results of the analysis of the distribution of type localities of Italian endemics to be a strategic tool for conservation planning and resource management. Application of plant micro-reserves and integration of diverse legislation tools are suggested to strengthen efforts and increase conservation success. Highlights: We provide the first large sale study on the distribution of 1536 type localities of Italian endemic plant species We highlight main drivers of distribution and major assets and for the conservation of type localities The distribution of the type localities should be taken into account in conservation planning